Qu'est-ce que la littérature, aujourd'hui? - Gans, Eric Lawrence (New literary history, 2007)
, The concept of Literature is associated with the emergence of national consciousness around 1800; its master genre is the novel. But in the developing consumer society of the nineteenth century, the novelist's fiction of authentic life becomes asymptotic to his own, culminating with Proust, whose novel is a series of intermittent narratives structured only by the ultimate realization of the narrator's literary vocation. This desultory structure is homologous to that of the blog, the auto-narrative of today's archival society. But although the ultimate narrative artwork is a series of semi-connected tales, we still need traditional novels and stories that give meaning to the life of desire.